2017
DOI: 10.18805/lr.v0i0.8411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sowing ratio and harvest periods on hay yields, quality and competitive characteristics of Hungarian vetch – cereal mixtures.

Abstract: Since Hungarian vetch has semi-decumbent stem, it is commonly grown in mixture to prevent lodging of plants. Hungarian vetch, barley, wheat and triticale were sown as pure and in vetch-cereal mixtures (70:30, 60:40, 50:50, 40:60) and harvested at two periods (pure cereals and mixtures were harvested at flowering and milk-dough stage of cereals; pure vetch was harvested at flowering and initial pod-set). Barley in all mixtures had negative impacts on development of Hungarian vetch. Considering hay yields, crud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
2
9
0
1
Order By: Relevance
“…Crude protein ratio of silage: Lowering seed ratio of BC in the mixture generally decreased the crude protein (CP) ratio of silage (Table 3). Our results were in agreement with other studies (Carpici, 2017;Acar et al, 2017) where legumes also increased CP concentrations when in mixture with cereals. In this respect, grass-legume mixtures have high crude protein concentration and low fiber concentration than pure grass stand Legumes are good source of protein and can be used to compensate cereal protein shortage (Gebrehiwot et al, 1996).…”
Section: Dry Matter (Dm) Yieldsupporting
confidence: 94%
“…Crude protein ratio of silage: Lowering seed ratio of BC in the mixture generally decreased the crude protein (CP) ratio of silage (Table 3). Our results were in agreement with other studies (Carpici, 2017;Acar et al, 2017) where legumes also increased CP concentrations when in mixture with cereals. In this respect, grass-legume mixtures have high crude protein concentration and low fiber concentration than pure grass stand Legumes are good source of protein and can be used to compensate cereal protein shortage (Gebrehiwot et al, 1996).…”
Section: Dry Matter (Dm) Yieldsupporting
confidence: 94%
“…As a result of the analysis of variance, there was no difference between mixtures in terms of LER and competition ratio (Table 6). However, it has been determined (Asci et al, 2015;Acar et al, 2017;Mut et al, 2017;Önal Aşcı and Eğritaş, 2017;Gulumser et al, 2018). The aggressivity and competition ratio of the plants have changed depending on the climate and mixture ratio and as a result of statistical analysis, the year × mixture interaction has been found significant (p<0.01) (Table 7-10).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Hungarian vetch is well recognized as a legume with the potential of increasing soil nitrogen (N) levels. It gives about 100 kg N ha -1 to the soil (Acar et al, 2017). However, since the plant has a thin stem, it starts to lodge after flowering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, the liquid fertilizer affected the shoot heights and root lengths in this study. The vetch structure is prone to bending problems in field studies, and it has been proposed to grow vetch with grains such as barley, wheat, triticale (Acar et al 2017), oats and rye (Yolcu et al 2009, Aşcı et al 2020. In this study, the best root length value for the triticale and vetch was found in the TV20%+LF group.…”
Section: Discussionmentioning
confidence: 99%